Linked Data and Knowledge Graph 7th Chinese Semantic Web Symposium and 2nd Chinese Web Science Conference, CSWS 2013, Shanghai, China, August 12-16, 2013. Revised Selected Papers - Qi, Guilin; Tang, Jie.; Du, Jianfeng; Pan, Jeff Z.; Yu, Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Seventh Chinese Semantic Web Symposium and the Second Chinese Web Science Conference, CSWS 2013, held in Shanghai, China in August 2013. The 14 revised full papers presented together with 6 short papers and 3 poster papers were carefully reviewed and selected from 48 submissions. The papers cover a wide range of topics, including semantic search, ontology reasoning, social semantic Web, knowledge graph, etc.
Semantic search -- Ontology reasoning -- Social semantic Web -- Knowledge graph.
Keywords: Computer science; Data mining; Artificial intelligence; Computer Science; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).